The Impact of Network Capability on Knowledge Creation and Business Performance: a Mediator Moderator Analysis - Pujianto, Wahyu Eko; Razli , Izyanti Awang; Putri, Bella May Ranti; Irawan, Nico (School of Business, IPB University (SB-IPB), 2025)
Background: Businesses face dynamic market challenges that ultimately affect businesses, especially SMEs. SMEs' success can be realized through network capability, facilitating access to markets, resources, information, and collaboration opportunities to support business competitiveness and growth.Purpose: Objective: This study examines and analyzes the effect of network capability in creating new knowledge on business performance, with knowledge creation as a mediator and agile capability as a moderator.Design/methodology/approach: This research was conducted in the food, beverage, furniture, fashion, electronics, textile, and beauty industries, involving 215 SMEs in East Java, including managers, SPVs, and decision-makers. A non-probability sampling technique was used for sample selection. Non-probability sampling methods are used to select respondents, while purpose sampling techniques focus on specific subgroups that have certain characteristics. Data analysis used quantitative methods, specifically Mplus 8 software, to test the research hypothesis.Findings/Result: The results showed that network capability significantly positively affects knowledge creation. Furthermore, network capability has a significant positive impact on business performance, mediated by knowledge creation. This study also found that the variable of knowledge creation on business performance moderated by agile capability does not strengthen. Agile capability did not moderate the relationship significantly, indicating that too much change or rapid adaptation can disrupt the consistency of long-term strategies, ultimately detrimental to overall business performance.Conclusion: This study shows that network capability positively affects knowledge creation and business performance while agile capability does not significantly moderate the relationship between the two, so further research can explore other variables, such as digital transformation capability. SME success can be realized through networking capability that facilitates access to markets, resources, information, and collaboration opportunities, supporting business competitiveness and growth in an evolving marketplace.Originality/value (State of the art): These findings contribute to the business by enhancing skill capabilitiy and fulfilling business advantages for business products. Keywords: network capability, knowledge creation, agile capability, business performance, and market dynamics